Effects of Combination of Inorganic and Organic Fertilizers Application on Morphology and Physiology of Immature Oil Palm - Fuady, Zahrul; Satriawan, Halus; Agusni, Agusni (Universitas Muhammadiyah Yogyakarta, 2019)
Oil palm requires nutrients both macro and micro nutrients for its growth and development processes. This study aimed to study the morphological and physiological responses of immature oil palm plantations at 1 year of planting to the provision of organic fertilizer and micro fertilizers as a complement to inorganic fertilizers.The research was arranged in a Randomized Completely Block Design (RCBD). The treatment applied consisted of 7 treatments, namely one control treatment (basic fertilizer) and six treatments from a combination of type and dose of fertilizer, consisting of single fertilizer, compound fertilizer, organic fertilizer and micro fertilizer. Based on the results, single and compound fertilizers accompanied by micro fertilizers (M1a, M1b) had a significant effect on plant height showing 13.78%, 27.55%, 25.11%, and 54.18% higher than others andon length and width of the 9th midrib reaching 7.47%, 22.40% and 51.04% better than others. The best response of growth of stem circumference at 6 MAT was observed in PO1 reaching 112.43%, better than M1a (111.96%)and M1b (109.20), while the lowest was observed in PO0 (97.84%). Meanwhile, chlorophyll and stomata were implied by a package of compound fertilizer and single fertilizer. The highest leaf chlorophyll content was in the M0a fertilizer treatment, while the highest stomata level was in the M1a treatment.